2017
DOI: 10.1039/c7cc05813f
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free diastereoselective construction of bridged ketal spirooxindoles via a Michael addition-inspired sequence

Abstract: A TfOH-catalyzed highly diastereoselective Michael addition/ketalization sequence of 3-hydroxyoxindoles and ortho-hydroxychalcones was developed, leading to biologically important bridged ketal spirooxindoles in moderate to excellent yields. Moreover, some chemical transformations were carried out to further extend the structural complexity and diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 56 publications
0
19
0
1
Order By: Relevance
“…To test the feasibility of our synthetic design, initially, ethyl 3-carboxylate-substituted isoindolinone 1 a and ortho-hydroxychalcone 2 a were selected as model substrates. Delightfully, the expected cascade cyclization proceeded successfully under the catalysis of triflic acid, delivering the bridged polycyclic isoindolinone 3 a in 79% yield ( [8][9][10][11]. The competitive chromene-substituted isoindolinone was not detected in our system in all cases.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…To test the feasibility of our synthetic design, initially, ethyl 3-carboxylate-substituted isoindolinone 1 a and ortho-hydroxychalcone 2 a were selected as model substrates. Delightfully, the expected cascade cyclization proceeded successfully under the catalysis of triflic acid, delivering the bridged polycyclic isoindolinone 3 a in 79% yield ( [8][9][10][11]. The competitive chromene-substituted isoindolinone was not detected in our system in all cases.…”
mentioning
confidence: 97%
“…Recently, we have found that ortho-hydroxychalcones were capable of behaving as bis-electrophiles to construct bridged cyclic compounds. [10] We rationalized that the reaction of 3carboxylate-substituted isoindolinone 1 and orthohydroxychalcones 2 may provide a convenient approach to access bridged polycyclic isoindolinones. As shown in Scheme 2b, this strategy involves a Michael addition process and subsequent hemiketalization/ dehydration to form the oxocarbenium ion intermediate A.…”
mentioning
confidence: 99%
“…Cyclodidemniserinol trisulfate (11), isolated by Faulkner et al in 2000, is an HIV-1 integrase inhibitor, was synthesized by Liu et al [49] A chiral pool approach towards the synthesis of 3,5,7trisubstituted-6,8-dioxabicyclo [3.2.1] octane core 170 of cyclodidemniserinol trisulfate was developed through I 2 -mediated intramolecular cyclisation. Recently, Yanshuo et al [50] developed a TfOH-catalyzed highly diastereoselective metal-free Michael addition/acetalization sequence of 3-hydroxy oxindoles 171 and ortho-hydroxy chalcones 172 to give an access to methanobenzodioxepine spirooxindoles 173, encapsulating a bridged bicyclic acetal motif, in moderate to excellent yields (Scheme 37). for 5 min to get the desired product 170 in 30 % yield (Scheme 36).…”
Section: Scheme 28 Synthesis Of Bicyclic Acetal Of (-)-Pinnatoxin Amentioning
confidence: 99%
“…[11] Based on this work and inspired by the synthetic charm of cascade reactions reported by us [12] and others, [13] we envisioned that similar cascade process may proceed if a trinucleophile with a pedant nucleophilic hydroxyl group and β,γ-unsaturated α-ketoester were chosen as the starting materials. [11] Based on this work and inspired by the synthetic charm of cascade reactions reported by us [12] and others, [13] we envisioned that similar cascade process may proceed if a trinucleophile with a pedant nucleophilic hydroxyl group and β,γ-unsaturated α-ketoester were chosen as the starting materials.…”
mentioning
confidence: 99%
“…Recently, we have achieved the highly diastereoselective construction of bridged O,O-and N,O-ketalspirooxindoles by reactions of 3-hydroxy/amino-oxindoles with ortho-hydroxychalcones through a Michael addition/ketalization sequence, where ortho-hydroxychalcones not only provided a nucleophilic hydroxyl group, but also was equipped with two electrophilic sites, thus enabling the cascade cyclization to construct bridged O,O-/N,O-ketals (Scheme 1, eq (1)). [11] Based on this work and inspired by the synthetic charm of cascade reactions reported by us [12] and others, [13] we envisioned that similar cascade process may proceed if a trinucleophile with a pedant nucleophilic hydroxyl group and β,γ-unsaturated α-ketoester were chosen as the starting materials. However, the key was to choose an appropriate tri-nucleophile to participate in the Michael addition-inspired cascade cyclization.…”
mentioning
confidence: 99%